Real Money Balances in the Production Function of a Developing Country - Khan, Ashfaque H.; Ahmad, Mushtaq (The Review of Economics and Statistics, 1985)
Real money balances as a factor input in the production function of the large-scale manufacturing sector in Pakistan has been examined in a multi-equation framework. Besides labor and capital, real money balances turned out to be an important factor of production. Our results are in accordance with the pioneering work of Sinai and Stokes in this area.